한국어판 사회적 의사소통 설문지 타당화 연구 - 김주현(Joo-Hyun Kim); 선우현정(Hyun-Jung Sunwoo); 박수빈(Su-Bin Park); 노동현(Dong-Hyun Noh); 정연경(Yeon Kyung Jung); 조인희(In-Hee Cho); 조수철(Soo-Churl Cho); 김붕년(Bung-Nyun Kim); 신민섭(Min-Sup Shin); 김재원(Jae-Won Kim); 박태원(Tae-Won Park); 손정우(Jung-Woo Son); et al. (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2015)
Objectives : The purposes of this study were to examine the reliability and validity of the Korean version of Social Communication Questionnaire (K-SCQ) and to determine cut-off scores for diagnosis of autism spectrum disorder (ASD). Methods : A total of 166 subjects with ASD and their 186 unaffected siblings were recruited through child psychiatry clinics of university hospitals. Board certified child psychiatrists screened all probands suspected to have ASD based on the Diagnostic and Statistical Manual of Mental Disorders, fourth edition. To confirm the diagnoses, the Korean versions of the Autism Diagnostic Observation Schedule and the Autism Diagnostic Interview-Revised (K-ADI-R) were administered to all the subjects. All parents completed the K-SCQ and Social Responsiveness Scale (SRS). The non-ASD siblings were evaluated with the same instruments as the probands with ASD. We performed a factor analysis to examine the structure of K-SCQ. For testing the validity of K-SCQ, we compared the difference in Lifetime and Current scores of probands with ASD and their non-ASD siblings using t-test and analysis of covariance. Correlations between the K-SCQ and other measurements of ASD symptomatology, including K-ADI-R totals and domain scores and SRS, were examined. Receiver operation characteristic curve analysis was performed to extract cutoff scores discriminating affection status. Results : Four factors were extracted through factor analysis of K-SCQ ; 1) social relation and play, 2) stereotyped behavior, 3) social behavior, and 4) abnormal language. Cronbach's internal consistency was .95 in K-SCQ Lifetime, and .93 in K-SCQ Current. There were significant differences in total score of K-SCQ, both in Lifetime and Current between the ASD group and non-ASD siblings group (p<.05). K-SCQ scores were significantly correlated with K-ADI-R subdomain scores and SRS total scores (p<.05). The best-estimate cut-off scores of K-SCQ for diagnosis of ASD were 12 for 48 months and over, and 10 for below 47 months. Conclusion : Our findings suggest that the K-SCQ is a reliable and valid instrument for screening autistic symptoms in the Korean population. Lower cut-off scores than the original English version might be considered when using it as a screening instrument of ASD.